HMGB1 and Extracellular Histones Significantly Contribute to Systemic Inflammation and Multiple Organ Failure in Acute Liver Failure - Runkuan Yang; Xiaoping Zou; Jyrki Tenhunen; Tor Inge Tønnessen (Mediators of Inflammation)
Acute liver failure (ALF) is the culmination of severe liver cell injury from a variety of causes. ALF occurs when the extent of hepatocyte death exceeds the hepatic regenerative capacity. ALF has a high mortality that is associated with multiple organ failure (MOF) and sepsis; however, the underlying mechanisms are still not clear. Emerging evidence shows that ALF patients/animals have high concentrations of circulating HMGB1, which can contribute to multiple organ injuries and mediate gut bacterial translocation (BT). BT triggers/induces systemic inflammatory responses syndrome (SIRS), which can lead to MOF in ALF. Blockade of HMGB1 significantly decreases BT and improves hepatocyte regeneration in experimental acute fatal liver injury. Therefore, HMGB1 seems to be an important factor that links BT and systemic inflammation in ALF. ALF patients/animals also have high levels of circulating histones, which might be the major mediators of systemic inflammation in patients with ALF. Extracellular histones kill endothelial cells and elicit immunostimulatory effect to induce multiple organ injuries. Neutralization of histones can attenuate acute liver, lung, and brain injuries. In conclusion, HMGB1 and histones play a significant role in inducing systemic inflammation and MOF in ALF.